Mortality and cause of death of Australians on the autism spectrum. Issue 5 (25th February 2019) - Hwang, Ye In (Jane); Srasuebkul, Preeyaporn; Foley, Kitty‐Rose; Arnold, Samuel; Trollor, Julian N.
Abstract : Focused investigations regarding mortality rates, risk factors, and cause of death in autistic populations remain scarce. The present study used large linked datasets spanning 2001–2015 to report the rates and risk factors for mortality and cause of death in individuals on the autism spectrum ( n = 35, 929 age range 5–64) with and without concurrent intellectual disability (ID) in New South Wales, Australia. Mortality rates for those on the autism spectrum were 2.06 times that of the general population. Concurrent ID, epilepsy, mental health conditions, and chronic physical health conditions were associated with a higher risk of death for those on the spectrum, whereas demographic variables such as gender and socioeconomic status were not. A differing profile of top causes of death was found for autistic individuals relative to the general population, with "nervous system and sense disorders" and "injury and poisoning" being the top‐ranked causes for those on the spectrum. The findings alert the need for health promotion and management of concurrent physical and mental health conditions for those on the autism spectrum. There is also a need for better identification, diagnosis, and documentation of older adults on the autism spectrum. Autism Research 2019, 12: 806–815 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Rates of death are higher for autistic individuals compared to the general population. There is higher risk of death for autistic individuals who have additional mental and physical health conditions. The leading causes of death for autistic individuals with and without ID are "nervous system and sense disorders", which includes epilepsy and "injury and poisoning", respectively. To minimize risk of death, it is important to manage the mental and physical health individuals on the autism spectrum and to better understand the circumstances surrounding preventable deaths for this population.